1975
DOI: 10.1016/0005-2736(75)90003-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chain length and lipid phase transitions on the selective permeability properties of liposomes

Abstract: SUMMARYThis paper describes experiments showing the importance of the fatty acid chain length on the barrier properties of liposomal bilayers, prepared from saturated lecithins, under conditions of lateral phase separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(90 citation statements)
references
References 25 publications
8
79
1
Order By: Relevance
“…Figure 4A shows the release of K ÷ from multilayered liposomes of DMPC and DMPE as a function of temperature. As shown before the liposomes of DMPC loose all their enclosed K + when incubated at temperatures in the vicinity of the gel to liquid-crystalline phase transition [1]. In contrast, such an increase in permeability could not be noticed in liposomes of DMPE.…”
Section: Raman Studiessupporting
confidence: 50%
See 1 more Smart Citation
“…Figure 4A shows the release of K ÷ from multilayered liposomes of DMPC and DMPE as a function of temperature. As shown before the liposomes of DMPC loose all their enclosed K + when incubated at temperatures in the vicinity of the gel to liquid-crystalline phase transition [1]. In contrast, such an increase in permeability could not be noticed in liposomes of DMPE.…”
Section: Raman Studiessupporting
confidence: 50%
“…For pure lecithin bilayers it has been demonstrated that ionic permeability [1][2][3], susceptibility for pancreatic phospholipase A2 degradation [4] and rate of transbilayer movement of lipid molecules [5] are markedly increased in the temperature range at which the hydrocarbon phase transition occurs. Two possible explanations have been given for the enhanced permeability in the vicinity of the gel to liquidcrystalline phase transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Solute leakage from liposomes rapidly accelerates when the components which constitute the liposomes cause phase separation. 15,18) However, CF leakage from liposomes in the gel state decreased with increasing mole fractions of DSPE-PEG, and was suppressed even for all PEG molecular weights. Therefore, in the gel state, the effect of phase separation on CF leakage can be decreased by decreasing the mobility of lipid molecules which constitute the liposomal bilayer membrane.…”
Section: Resultsmentioning
confidence: 97%
“…Under physiological conditions, the immobile phospholipid fraction was immobilized to the cytoskeleton or to the extracellular matrix. The lateral diffusion properties of the lipid bilayer depended on the lipid content (Blok et al, 1975;Cullis, 1976): Both the amount of cholesterol and the head group composition of the phospholipids, as well as the acyl composition determine the fluidity of the membrane. Below the so called phase transition temperature, the fluid lipids will enter a frozen state in which they do not show lateral diffusion (Feigenson, 1976).…”
Section: Detection Of Lateral Diffusionmentioning
confidence: 99%